Decoding the transcriptomics of oil palm seed germination - Suksa-Ard, Padungsak; Nuanlaong, Sunya; Pooljun, Chettupon; Mohamad Azzeme, Azzreena; Suraninpong, Potjamarn (Multidisciplinary Digital Publishing Institute, 2024)
Seed dormancy and germination are critical factors affecting oil palm production efficiency. The typical dormancy-breaking process involves dry heat treatment (38–40 °C for 40–60 days) followed by germination at 30–32 °C. To understand the molecular mechanisms behind this process and improve germination rates and speed, we conducted transcriptome analysis at three stages: pre-incubation, 45-day incubation at 40 °C, and 14-day germination at 32 °C. Our findings, supported by qRT–PCR and DEGs analysis, identified four key stages: ABA degradation, energy mobilization, starch mobilization, and cell elongation and division. ABA pathway genes (SnRK2, PYR/PYL) were active during dormancy release, while GAE and GPI were upregulated after heat treatment, indicating increased energy metabolism and structural changes. During germination, genes involved in starch/sucrose metabolism (SPS, TPP, SS, MGAM) and cell wall biosynthesis (GAUT1, PE, GAE) supported embryo expansion, with BAM, PGM, GlgB fueling early growth. Auxin (TIR1, AUX/IAA, ARF), brassinosteroid (BRI1, BSK, BIN2, CYCD3), ethylene (ETR, CTR1), and jasmonic acid (JAR1, COI1) pathway genes regulated cell growth and stress response, promoting seedling development. Though gibberellins were not crucial for this oil palm variety, gene expression varied between varieties. This study provides information on oil palm seed germination that could be applied to other oil palm species, particularly in terms of incubation times and chemical treatments.